(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This article explores the role and significance of the chronotope in literary works. Based on M. Bakhtin’s theory of chronotope, the unity of time and space in artistic works is analyzed as fundamental factors shaping the plot, composition, and characters. The manifestation of the chronotope in Uzbek novellas, its national and cultural peculiarities, as well as its role in highlighting the psychological experiences and worldview of characters, are discussed. Locations such as villages, cities, mountains, and deserts are analyzed as elements that complement the artistic and aesthetic content of the work